ABUSE OF CIRCUMSTANCES AS A CAUSE OF THE AVOIDATION OF CONTACT IN THE CIVIL COURT AND ISLAMIC LAW - Shodiq, Ja'far; Albab, Ulil; Amalia Putri, Erika Husna (Jurnal Independent, 2022)
Abstraction This research is library research. Regarding the termination of an engagement in the KUHper, Article 1381 explicitly mentions ten ways to terminate an engagement. These methods are: Payment, offer of cash payment followed by deposit or safekeeping (consignment), debt renewal (novation), debt settlement or compensation, debt mixing (confucio), debt relief, obliteration of outstanding goods, cancellation/cancellation, entry into force a condition is void, and the lapse of time (expiration). Indeed, freedom of contract stems from the position of both parties being equally strong, having the same bargaining position, so that each party is domiciled as a contract partner. . The reality is not so, in making a contract each party, especially the party who is in a strong economic position, tries to seize dominance over the other party and face each other as opponents of the contract. The party whose position is stronger can impose his will on the other party for his own benefit, resulting in the content and terms of the contract being one-sided or unfair.